Fibre – Need to increase intake according to new recommendations. Issue 4 (December 2015) - Buttriss, J. L.
Abstract: In its report on Carbohydrates and Health, the Scientific Advisory Committee on Nutrition (SACN) has recommended increases in the dietary reference values for fibre to 30 g/day for adults and 15–30 g/day for children, depending on their age. Intakes are currently much lower than this, at an average of 18 g/day in adults, less in children, and there are socio‐economic differences, with lower intakes in the lowest income quintile compared to the highest. Dietary modelling shows that achieving these recommendations is possible but will require substantial changes to dietary patterns for many, with meals based around fibre‐rich starchy foods (such as wholegrain and high‐fibre options of bread, breakfast cereals, pasta and rice, and jacket potatoes), supplemented by inclusion of high‐fibre snacks such as unsalted nuts and considerable amounts of vegetables and fruit, daily. This article discusses the challenges associated with communicating these new recommendations, in the context of current labelling legislation.